A course in applied economics - Brown, Ernest Henry Phelps; Wiseman, Jack (London : I. Pitman, 1964)
The course covered all the main applications of economics,in the systematic and comprehensive way
Includes bibliographical references and index.
obn 23/01/2019
Loans
Keywords: Economics; Economic policy